The Phenomenon of Divorce and Its Impact on Changes in Family Structure and Dynamics in the Millennial and Z Generations - Aini, Syarifah; Kamaruddin, Syamsu; Tenri Awaru, Andi Octamaya (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract: This study discusses the phenomenon of divorce, how the description of the divorce phenomenon and its impact on changes in family structure and dynamics in two generations, namely millennials and Z, using a literature study method in the form of studies conducted only based on books, journals, scientific articles and news sites. The purpose of this article is to provide an overview of the phenomenon of divorce and its impact on changes in family structure and dynamics in the millennial and Z generations so that in the future in facing all challenges and in making decisions regarding married life can be taken into account and considered carefully in terms of avoiding problems that may occur. The results of the literature study show that the factors that cause divorce are economic problems, infidelity, domestic violence and communication that is less effective in building a marital relationship. The impact on the family structure is to change the role, function, education of children, and parenting of children. All forms of change will change various conditions from structured because of the marital relationship to changing due to separation. The impact of family dynamics that occur is a change in communication patterns, which become tense due to conflict and children find it difficult to adapt to the new atmosphere and conditions after divorce.